2017
DOI: 10.1097/rlu.0000000000001540
|View full text |Cite
|
Sign up to set email alerts
|

FDOPA PET-CT of Nonenhancing Brain Tumors

Abstract: Including data from amino acid metabolism used alone or in association with MRSI allows us to discriminate between dysembryoplastic neuroepithelial tumor and grade II oligodendroglioma and between low- and high-grade gliomas with no contrast enhancement on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…In our previous study on brain metastases [ 17 ] and in the present study, a significant [18F] FDOPA uptake (defined by a ratio SUVmax T/S >0.75) in tumours was correlated with a LAT1 score higher than 100, suggesting that, as expected, LAT1 expression may play an important role in [18F] FDOPA uptake and that a minimal LAT1 expression is required for [18F] FDOPA uptake. The lack of direct correlation between the level of LAT1 expression and the level of intensity of [18F] FDOPA uptake in our study may be due to several reasons: sampling and intra-tumour heterogeneity, small size of our series and heterogeneity of tumours (gliomas and metastases), interferences with other factors influencing [18F] FDOPA uptake such as tumour grade [ 22 24 ] and treatments [ 20 ].…”
Section: Discussionmentioning
confidence: 80%
“…In our previous study on brain metastases [ 17 ] and in the present study, a significant [18F] FDOPA uptake (defined by a ratio SUVmax T/S >0.75) in tumours was correlated with a LAT1 score higher than 100, suggesting that, as expected, LAT1 expression may play an important role in [18F] FDOPA uptake and that a minimal LAT1 expression is required for [18F] FDOPA uptake. The lack of direct correlation between the level of LAT1 expression and the level of intensity of [18F] FDOPA uptake in our study may be due to several reasons: sampling and intra-tumour heterogeneity, small size of our series and heterogeneity of tumours (gliomas and metastases), interferences with other factors influencing [18F] FDOPA uptake such as tumour grade [ 22 24 ] and treatments [ 20 ].…”
Section: Discussionmentioning
confidence: 80%
“…Bund et al analyzed 33 patients with nonenhancing primary brain tumors. An optimal threshold of SUV max T/ N = 2.16 (AUC = 0.87) discriminated low-grade from high-grade gliomas with 60% sensitivity, 100% specificity, 100% PPV, and 83.3% NPV ( p < 0.01) [ 29 ]. Moreover, the authors reported that 18 F-FDOPA was also useful in the subgroup of low-grade gliomas.…”
Section: Resultsmentioning
confidence: 99%
“…At initial presentation, contrast-enhancement (CE) on the magnetic resonance imaging (MRI) scan, the gold standard for diagnosis and response assessment in malignant gliomas [5], may suggest a high-grade glioma (HGG), and up to 51% of newly-diagnosed GBMs may contain non-enhancing cortical signal abnormality [6]. In a prospective study of 53 newly-diagnosed brain tumor patients with non-CE lesions on MRI, 34% were found to have histologically-proven high-grade glioma [7].…”
Section: Introductionmentioning
confidence: 99%